The Case for International Coordination of Electricity Regulation : Evidence from the Measurement of Efficiency in South America - Estache, Antonio 1957- (The World Bank, 2002)
A decade long experience shows that monitoring the performance of public and private monopolies in South America is proving to be the hard part of the reform process. The operators who control most of the information needed for regulatory purposes have little interest in volunteering their dissemination unless they have an incentive to do so. Estache, Rossi, and Ruzzier argue that, in spite of, and maybe because of, a much weaker information base and governance structure, South America's electricity sector could pursue an approach that relies on performance rankings based on comparative efficiency measures. The authors show that with the rather modest data currently available publicly, such an approach could yield useful results. They provide estimates of efficiency levels in South America's main distribution companies between 1994 and 2000. Moreover, the authors show how relatively simple tests can be used by regulators to check the robustness of their results and strengthen their position at regulatory hearings. This paper—a joint product of the Governance, Regulation, and Finance Division, World Bank Institute, and the Finance, Private Sector, and Infrastructure Unit, Latin America and the Caribbean Region—is part of a larger effort in the institute to increase understanding of infrastructure regulation